2016
DOI: 10.1128/jb.00696-15
|View full text |Cite
|
Sign up to set email alerts
|

Structural Similarities and Differences between Two Functionally Distinct SecA Proteins, Mycobacterium tuberculosis SecA1 and SecA2

Abstract: While SecA is the ATPase component of the major bacterial secretory (Sec) system, mycobacteria and some Gram-positive pathogens have a second paralog, SecA2. In bacteria with two SecA paralogs, each SecA is functionally distinct, and they cannot compensate for one another. Compared to SecA1, SecA2 exports a distinct and smaller set of substrates, some of which have roles in virulence. In the mycobacterial system, some SecA2-dependent substrates lack a signal peptide, while others contain a signal peptide but p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Our analysis was consistent with the findings of our modeling attempt, which among the available structures of SecY-bound SecA conformation lacked a suitable template for the interaction site of the target protein that connects the two β-strands of the PPXD to NBD1 in CDSecA2 ( Figure 3A,B and Figure S2). In addition, the SecY channel interaction region is located at the 2HF loop and its surrounding area [23,24,59], where high surface residue conservation suggests their conserved functional role ( Figures 3C and 5 and Figures S2 and S3). Namely, superimposition of our CDSecA2-SecY-bound conformation model with the T. maritima SecA-SecY structure (PDB ID 3DIN; [24]) showed structural similarities that would lead to the PPXD with its loops and the long helix of the HSD forming the contact surface with the SecY channel and the 9-residue-long and flexible 2HF loop inserting into the SecY channel (residues L742-P750; Figure 3C and Figures S2 and S3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis was consistent with the findings of our modeling attempt, which among the available structures of SecY-bound SecA conformation lacked a suitable template for the interaction site of the target protein that connects the two β-strands of the PPXD to NBD1 in CDSecA2 ( Figure 3A,B and Figure S2). In addition, the SecY channel interaction region is located at the 2HF loop and its surrounding area [23,24,59], where high surface residue conservation suggests their conserved functional role ( Figures 3C and 5 and Figures S2 and S3). Namely, superimposition of our CDSecA2-SecY-bound conformation model with the T. maritima SecA-SecY structure (PDB ID 3DIN; [24]) showed structural similarities that would lead to the PPXD with its loops and the long helix of the HSD forming the contact surface with the SecY channel and the 9-residue-long and flexible 2HF loop inserting into the SecY channel (residues L742-P750; Figure 3C and Figures S2 and S3).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HWD interacts with C-terminal part of the SecY in crystal structures of SecA-SecY(EG) complexes [ 24 , 29 ] and with adjacent lipids [ 30 ]. Thus, the lack of HWD in SecA2 systems may enable binding of specific substrates by increasing solvent exposure of the target recognition site [ 23 ] and hamper binding of SecA2 to SecYEG. We showed that the conformation of CDSecA2 HWD closely resembles those of the general SecA systems ( Figure 1 C), thereby suggesting CDSecA2 may bind to SecYEG and participate in substrate recognition and translocation in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, M. tuberculosis SecAl and SecA2 share only 38% identity (54% sequence similarity). Thus, it was a surprise to discover broad similarity between the crystal structures of M. tuberculosis SecAl and SecA2 (80). However, compared to SecAl, the CTD of SecA2 is truncated, similar to what was found for SecA2 of the aSec system (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the helical wing domain (HWD) is missing in the mycobacterial SecA2. The lack of an HWD is a conserved feature of actinobacteria SecA2 proteins, but small HWD truncations may also exist in other SecA2 proteins (80). The significance of CTD and HWD truncations to SecA2 function remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%